Law and the arms trade : weapons, blood and rules - Lustgarten, Laurence (Oxford, England : Hart Publishing, 2020)
"This ground-breaking book offers an extensive legal analysis-grounded in public law, EU, and international law-of arms trade regulation, integrated with insights drawn from international relations. The sale of weapons and related technologies is, globally, one of the most politically controversial and ethically contentious forms of commerce. Intimately connected with sustaining repressive governments and violations of international human rights and humanitarian law, arms exports are also a central element in the economic and strategic policies of the governments of all large industrial states. They have also been the source of abundant corruption, and of serious challenges to the norms and effectiveness of constitutional accountability in democratic states. On paper, the arms trade is heavily regulated: national legislation and international treaties are in place which purport to prohibit certain transactions and limit others. Yet despite its importance, legal and international relations scholarship on the subject has been surprisingly limited. This book fills this gap in the literature by examining and comparing the export control regimes of eight leading nations - the USA, Russia, the UK, France, Germany, Sweden, China, and India - with chapters contributed by leading experts in the field of law and international relations"--
The arms trade : a critical introduction -- Governing arms transfers : the praxis of law and the evaluation of risk -- Fragile underpinning : the limits of EU Rules -- The EU criteria : a critical examination -- The UK : institutional and legal innovation, dangerous dependency -- The German control regime on arms exports -- Arms exports in France -- Sweden's arms export controls : balancing support and restraint -- The United States and arms exports -- Russian arms exports -- China as an arms exporter : the strategic contours of China's arms transfers -- India and arms exports -- Arms transfer regulation beyond national borders -- The arms trade treaty : a measure of global governance -- Future directions.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Arms transfers -- Law and legislation; International law; Electronic books